ANALISA IDENTITAS "BRANDING KOPI DULU" - Dwi Ramayanti (Narada : Jurnal Desain dan Seni, 2020)
Coffee is a popular drink in the world. Coffee lovers in Indonesia are increasing day by day. This is marked by the proliferation of coffee shop businesses in various cities throughout Indonesia. The coffee shop business is a promising business. This is due to the growing trend of drinking coffee in coffee shops or so-called hanging out, a lifestyle and a means of showing the existence of adults to adolescents, men, and women. Depok City has many coffee shops spread across eleven sub-districts, each of which has four to six sub-districts. This research was conducted at a coffee shop in the Sukmajaya district, Depok. The analytical method used is a visual review methodology of visual communication design elements analysis on branding identity. Visual communication design elements such as typography, layout, colors, illustrations/ photography/ images and branding identity elements such as brands (brands, logos) which can be visual, text, or both then color (product, corporate) the composition of all the constituent elements and promotional media as well as information media.